Performance of Isolated Footing with Several Corrosion Levels under Axial Loading - Ahmed Youssef; Mahmoud Hegazy; Hatem Mostafa (Civil Engineering Journal, 2023)
This research aims to illustrate the corrosion process and its effect on the deterioration of reinforced concrete (RC) isolated footings using a small-scale model (1/8) and present the results of a prototype-scale study using a numerical model with different concrete depths and corrosion levels under axial load. The experimental program consisted of testing five small-scale (1/8) model RC isolated footings under axial loading after subjecting them to accelerated corrosion tests with a constant current. The main variable in the small-scale sample test was the corrosion level. This study presents an experimental approach, using the constant current method and the finite element method (FEM) with the ABAQUS package, to examine its effect on the axial load behavior under different corrosion ratios, which were 0%, 4.21%, 9.11%, 24.56%, and 30.67%. On the prototype scale, the variables were the corrosion level and the RC depths of 300 mm, 400 mm, and 500 mm. The results indicated that the average deviation in ultimate load between the experimental and FEM outcomes for the small-scale was below 5.6%, while the average deflection deviation was 6.8%. Also, the study found that an increase in the depth of the RC footing and corrosion ratio led to a more pronounced impact of the cracking pattern in the concrete and corroded bars, as well as a greater difference in the failure load. The experimental results suggest that the proposed numerical model is accurate and effective. These findings have important implications for the evaluation of isolated footings affected by corrosion damage using FEM, and can help inform decisions related to their design and maintenance. The failure loads of non-corroded footings with different depths were compared with the ECP-203 provisions of the 2018 Egyptian Code, and how corrosion ratios can be simulated by numerical models. The percentage variation between the design loads by code and the numerical loads by ABAQUS for controlled footings with thicknesses of 300, 400, and 500 mm was found to be 73%, 80%, and 78%, respectively. Using the derived relationship, the equivalent corrosion ratio percentages were 23.8%, 20.2%, and 32%, respectively. Doi: 10.28991/CEJ-2023-09-06-011 Full Text: PDF